1995
DOI: 10.1074/jbc.270.2.860
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Drosophila Mitochondrial DNA Polymerase by Single-stranded DNA-binding Protein

Abstract: Mitochondrial DNA polymerase from Drosophila embryos has been characterized with regard to its mechanism of DNA synthesis in the presence of single-stranded DNA-binding protein from Escherichia coli. The rate of DNA synthesis by DNA polymerase gamma was increased nearly 40-fold upon addition of single-stranded DNA-binding protein. Processivity of mitochondrial DNA polymerase was increased approximately 2-fold, while its intrinsic rate of nucleotide polymerization was unaffected. Primer extension analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 42 publications
5
35
0
Order By: Relevance
“…In parallel with the stimulation profiles, we observed that mtSSB predominantly enhances primer utilization to increase the extent of DNA synthesis, with only a modest effect on DNA product strand length, which we determined in this analysis to be ϳ760 nt in the absence of mtSSB up to ϳ1100 nt in its presence. This effect is similar to that described previously for Pol ␥ from D. melanogaster and with the processivity of human Pol ␥ calculated from single nucleotide incorporation assays (12,22,23).…”
Section: Dna Polymerization Activity Of Pol ␥ Depends On the Molarsupporting
confidence: 71%
“…In parallel with the stimulation profiles, we observed that mtSSB predominantly enhances primer utilization to increase the extent of DNA synthesis, with only a modest effect on DNA product strand length, which we determined in this analysis to be ϳ760 nt in the absence of mtSSB up to ϳ1100 nt in its presence. This effect is similar to that described previously for Pol ␥ from D. melanogaster and with the processivity of human Pol ␥ calculated from single nucleotide incorporation assays (12,22,23).…”
Section: Dna Polymerization Activity Of Pol ␥ Depends On the Molarsupporting
confidence: 71%
“…We would suggest that this derives from a different mechanism, because both these and the parent deletion mutant ⌬␥3 retain strong subunit interactions that are comparable with wild-type pol ␥. One interesting possibility is that the reduced processivity of the L558A and F578A mutants is related to defective interaction with mtSSB, a factor that increases strongly both the activity and processivity of wild-type DNA pol ␥ (37,39). Notably, the stimulation of DNA polymerase activity on M13 DNA by mtSSB is reduced 4 -5-fold in the L558A and F578A mutant holoenzymes as compared with wild type (6 -7-versus 30-fold stimulation).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulatory effects of mtSSB are minimal at higher salt concentrations where activity is high and processivity is reduced. Although wild-type mtSSB enhances proces- 4 , dsRNA and exogenous mtSSB mRNA were induced. Induction of dsRNA triggers degradation of endogenous mtSSB mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…7 was determined by Southern blot analysis. DNAs were isolated as described under "Experimental Procedures" after growth for 10 days in the presence or absence of 0.4 mM CuSO 4 . A fragment of the ATPase6 gene was used as the probe for determination of mtDNA content, and a DNA fragment from the nuclear histone gene cluster was used for normalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation